TEACHER'S OPINION ON HOLISTIC AND MULTIDISCIPLINARY EDUCATION IN THE CONTEXT OF NEP-2020 - Sarkar, Sonal; Dave, Anjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The “Ministry of Human Resource Development (MHRD) of India” has recently introduced the National Education Policy (NEP) 2020, with the objective of providing equitable access to a superior standard of education for all students, via a comprehensive transformation of the country's educational framework. The primary objective of NEP 2020 is to enhance the educational system by making it more comprehensive, adaptive, and multidisciplinary, in order to better equip students for the difficulties of the contemporary world. The primary objective of the survey was to assess the opinions of educators about India's National Education Policy 2020. Furthermore, this research aims to establish the relationship between teachers' perspectives on the qualities of NEP 2020 and criteria like as gender, disciplinary background, and years of teaching experience. This study employs a descriptive research technique. The researcher employed the Purposive Stratified Sampling methodology to collect a total of 354 samples using internet channels. The researcher employed the eight attributes of NEP 2020 to create and establish a questionnaire with a score system consisting of five points. It was ascertained that it was trustworthy and authentic. In this study, statisticians utilized several statistical methods such as Sum, Mean, Percentage, and Chi-Square. The findings indicated a strong consensus among teachers and a little amount of divergence in their views about NEP. Furthermore, the analysis revealed that there was no notable correlation between teachers' endorsement and rejection (viewpoint) of the components of NEP 2020 and their gender or academic field. However, a significant connection was found with teachers' years of teaching experience. If India's educational system undergoes a significant transformation with new rules, all kids in the country will have the opportunity to get a high-quality education. Furthermore, it will promote the comprehensive development of the future residents of the nation.